2015
DOI: 10.1007/s00220-015-2490-x
|View full text |Cite
|
Sign up to set email alerts
|

Metric Projective Geometry, BGG Detour Complexes and Partially Massless Gauge Theories

Abstract: Abstract. A projective geometry is an equivalence class of torsion free connections sharing the same unparametrised geodesics; this is a basic structure for understanding physical systems. Metric projective geometry is concerned with the interaction of projective and pseudo-Riemannian geometry. We show that the BGG machinery of projective geometry combines with structures known as Yang-Mills detour complexes to produce a general tool for generating invariant pseudo-Riemannian gauge theories. This produces (det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…It turns out that 1 Formally, the compactifications [9,10] and its (A)dS counterparts [7,8] may be viewed as projectively reducing on a conformal hypersurface. This viewpoint was further studied for partially massless spin-two system in [11]. Starting from non-unitary conformal gravity, this work showed that projective reduction yields partially massless spin-two system, which is also non-unitary.…”
Section: Jhep11(2016)024mentioning
confidence: 95%
See 1 more Smart Citation
“…It turns out that 1 Formally, the compactifications [9,10] and its (A)dS counterparts [7,8] may be viewed as projectively reducing on a conformal hypersurface. This viewpoint was further studied for partially massless spin-two system in [11]. Starting from non-unitary conformal gravity, this work showed that projective reduction yields partially massless spin-two system, which is also non-unitary.…”
Section: Jhep11(2016)024mentioning
confidence: 95%
“…10 In the path integral formulation, this amounts to choosing that the integration contour purely imaginary. 11 Here, we define the mass-squared equal to the mass-squared in flat space limit. Therefore, it differs from the mass-squared dictated by the Fierz-Pauli equations.…”
Section: Jhep11(2016)024mentioning
confidence: 99%
“…The field equations for the metric and connection can be examined independently [42][43][44][45] in the context of Gauss-Bonnet, and because we are in four-dimensions, metric compatibility is still a solution to the field equations. Also, we have already mentioned in section 3 that when one of the members of a projective equivalence class [Γ a bc ] is a metric compatible connection, the projective Schouten tensor collapses to a constant times the metric [40,41]. D ab is that projective Schouten tensor when it is not dynamical.…”
Section: The Diffeomorphism Field Actionmentioning
confidence: 99%
“…[3.13] we recognizes D ab as precisely the projective Schouten tensor and Eq. [3.14] as λ times the projective Cotton-York tensor, [32][33][34]. From the projective curvature tensor, we calculate the components of the projective Ricci tensor K αβ ≡ K ρ αβρ to be,…”
Section: )mentioning
confidence: 99%
“…This metric coincides with metric projective tractors at a certain scale [34,39,40,33,32,30]. To guarantee finite volume when λ is integrated from 0 to ∞ in the action functionals, we choose f (λ) so that…”
Section: The Metric G αβ and Spin Connectionω Ab µmentioning
confidence: 99%